(untitled) (Journal of Bangladesh Academy of Sciences, 2011)
The thermal treatment of [Ru2(CO)6(μ-η1,η2-C4H3O)μ-P(C4H3O)2] 1 with dimethyl acetylenedicarboxylate (DMAD) at 110 °C leads to cyclotrimerization of DMAD. The cyclotrimerization product hexamethyl benzenehexacarboxylate, [C6(COOCH3)6] 2, was obtained in 37% yield and characterized by a combination of spectroscopic data and single crystal X-ray diffraction study. Compound 2 crystallizes in the monoclinic space group P1bar with a = 10.3002(12), b = 11.0371(13), c = 18.781(2) Å, α = 76.148(2), β = 87.390(2), γ = 74.001(2)°, Z = 4 and V = 1992.2(4) Å3. Key words: Cyclotrimerization; Dimethyl acetylenedicarboxylate; X-ray structure DOI: 10.3329/jbas.v34i2.6866 Journal of Bangladesh Academy of Sciences, Vol. 34, No. 2, 197-200, 2010